2022
DOI: 10.1155/2022/3225211
|View full text |Cite
|
Sign up to set email alerts
|

Bioinspired Crosslinked Nanocomposites of Polyvinyl Alcohol‐Reinforced Cellulose Nanocrystals Extracted from Rice Straw with Ethanedioic Acid

Abstract: In this study, cellulose nanocrystals (CNC) were extracted from rice straw and incorporated into polyvinyl alcohol (PVOH) as reinforcement nanofillers. Multiple nanocomposites with different CNC contents were prepared. Extracted CNC appear as long, well-defined rodlike crystals with a high aspect ratio (41). Nanocomposites with 3 wt% of CNC significantly exhibit improved tensile strength (60.4%) and maximum degradation temperature (287°C). Moreover, they demonstrate a decrease in water vapor permeability rate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 83 publications
0
1
0
1
Order By: Relevance
“…Previous studies hypothesized that the thermal stability of the composites was improved when the CNC had good interfacial interactions with the matrix . As shown in Figure B, Wang et al observed the thermal stability of the composites was improved, which was attributed to the good dispersibility of the CNC , and the hydrogen bonding network in the matrix . Thus, a well-dispersed CNC will delay the thermal degradation process of the material, resulting in an improved degradation temperature. , The well-dispersed CNC can act as a thermal barrier and mass transfer barrier during the decomposition process to improve the thermal stability of the material.…”
Section: Indirect Evaluationmentioning
confidence: 96%
“…Previous studies hypothesized that the thermal stability of the composites was improved when the CNC had good interfacial interactions with the matrix . As shown in Figure B, Wang et al observed the thermal stability of the composites was improved, which was attributed to the good dispersibility of the CNC , and the hydrogen bonding network in the matrix . Thus, a well-dispersed CNC will delay the thermal degradation process of the material, resulting in an improved degradation temperature. , The well-dispersed CNC can act as a thermal barrier and mass transfer barrier during the decomposition process to improve the thermal stability of the material.…”
Section: Indirect Evaluationmentioning
confidence: 96%
“…Se comprobó que, la celulosa bacteriana (BC) ha tenido un tenido un gran realce, porque se ha utilizado de gran manera en el ámbito de la electrónica flexible, dispositivos biomédicos, cosméticos, ingeniería de tejidos, liberación de fármacos, debido a su excelente seguridad y confiabilidad. También por las buenas propiedades conductivas que posee, al ser aplicados rellenos conductivos (CNT y PP), esto ayudaría a incrementar aun las incompuesto fibras de BC conductivo, con el fin de innovar con la tecnología ecológicas y biodegradable, a fin de recolectar energía portátil [18].…”
Section: Conclusionesunclassified

Cellulose Nanoparticles:systematic Review

Alfaro Flores,
Álvarez Quiroz,
Asato Cerna
et al. 2024
goi